2015
DOI: 10.3109/00365521.2015.1027261
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment of differences in the duodenal microbiome in subjects with irritable bowel syndrome

Abstract: 16S rDNA sequencing confirms microbial overgrowth in the small bowel in IBS, with a concomitant reduction in diversity. qPCR supports alterations in specific microbial populations in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 47 publications
3
64
0
1
Order By: Relevance
“…Among them, in the duodenum of IBS‐D patients, Aeromonas decreased and Shinella , Pseudoclavibacter , Leptothrix , and Polaromonas increased. These results were partially consistent with an earlier study of small luminal microbiota in IBS, which found that the frequency of Escherichia , Shigella , and Aeromonas was increased, whereas that of Acinetobacter , Citrobacter , and Microvirgula decreased . Here, we found that the frequency of Faecalibacterium was decreased in the rectum of IBS‐D patients, which was supported by a study by Carroll et al .…”
Section: Discussionsupporting
confidence: 93%
“…Among them, in the duodenum of IBS‐D patients, Aeromonas decreased and Shinella , Pseudoclavibacter , Leptothrix , and Polaromonas increased. These results were partially consistent with an earlier study of small luminal microbiota in IBS, which found that the frequency of Escherichia , Shigella , and Aeromonas was increased, whereas that of Acinetobacter , Citrobacter , and Microvirgula decreased . Here, we found that the frequency of Faecalibacterium was decreased in the rectum of IBS‐D patients, which was supported by a study by Carroll et al .…”
Section: Discussionsupporting
confidence: 93%
“…are mostly seen in patients with blind loop syndrome such as patients with Billroth II procedure (2). Currently a bacterial concentration of >10 3  c.f.u./ml is generally considered significant (41, 42, 44, 45). …”
Section: Resultsmentioning
confidence: 99%
“…Small intestinal bacterial overgrowth may be a contributing factor, with culture-based methods indicating higher levels of duodenal microbial populations in patients with IBS compared to healthy controls [43] . In addition, a recent study that used deep sequencing to analyse duodenal aspirates demonstrated the presence of greater levels of Escherichia coli , Klebsiella and Aeromonas species in IBS patients relative to controls [44] . Concurrent dysregulation of bile acid metabolism may play a significant role in disease pathogenesis, particularly in IBS-D, as a significant proportion of patients display evidence of bile acid malabsorption, which is likely to contribute to increases in colonic secretion [45] .…”
Section: Irritable Bowel Syndrome and Diarrheamentioning
confidence: 99%